Gold nanoparticle-decorated graphene as a nonlinear optical material in the visible and near-infrared spectral range. Issue 27 (3rd July 2018) - Kinastowska, K.; Piela, K.; Gordel, M.; Żak, A.; Kołkowski, R.; Samoć, M.
Abstract : The nonlinear absorption performance of plasmonic nanoparticle-decorated graphene sheets in aqueous dispersion has been investigated over a broad spectral range using the f-scan technique. Abstract : There have been numerous reports of boosting nonlinear optical phenomena in plasmonic nanostructures through local-field enhancement as well as through intrinsic metal nonlinearities. Here, we study the possibility of plasmonic enhancement of graphene's nonlinear absorption by creating a composite material: gold nanoparticle-decorated graphene dispersed in water. To evaluate the additive effect of combining the two materials on the saturable absorption efficiency we performed a series of f-scan (modified Z-scan) measurements using femtosecond laser pulses in the broad spectral range from 530 to 1600 nm. These studies are supplemented by TEM, UV-vis, ATR and Raman spectroscopy, revealing the mechanisms behind the formation of the composite material.